Seismic performance of long cable-stayed bridge with various time history loading using finite element method. Issue 1 (June 2020) - Aizon, Nabila Huda; Adnan, Azlan; Ramli, Mohd Zamri; Arjuna, Norazah; Alel, Asmawisham; Muhammad Yuzir, Muhamad Ali
Abstract: Recently, numerous natural disaster events have occurred in various parts of the world. Bridges are one of the most critical structures to be examined to check for defects resulting from disaster events like earthquakes. Therefore, the serviceability of the structure is important to maintain the safety of users. Thus, the main objective of this work is to study the seismic response of a cable-stayed bridge under earthquake time history loading. The cable-stayed bridge components (deck, piers, pylons, and cables) were modelled using finite element modelling in three dimensional (3D). Two types of seismic analysis was implemented in this study; Free Vibration Analysis (FVA) and Nonlinear Time History (NLTH) direct integration analysis to obtain the bridge seismic performance under the earthquake loading. A total of eight earthquake loads in scaled Peak Ground Acceleration (PGA) values of 0.75g, 1.0g, and 1.5g to represent low, moderate and strong earthquake loads, respectively, were used for the analysis. First, eight mode shapes with component directional and period are presented for free vibration analysis. Meanwhile, the NLTH direct integration analysis results reveal the time detection of seismic cable-stayed damage levels under certain peak ground accelerations (PGA). It can be concluded that the long cable-stayed bridge is not safe under several earthquake loads due to different earthquake load profiles. The results are also important to aid further damage assessment of the cable-stayed type of bridge.